2011
DOI: 10.1128/iai.00849-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Factor H-Binding Protein Sequence Variation on Factor H Binding and Survival ofNeisseria meningitidisin Human Blood

Abstract: Binding of the complement inhibitor factor H (fH) to the surface of Neisseria meningitidis is critical for evasion of innate host defenses. The meningococcal vaccine candidate factor H-binding protein (fHbp) serves as an fH ligand. We prepared 16 recombinant fHbp natural sequence variants. By enzyme-linked immunosorbent assay (ELISA), the variants from a New Zealand epidemic strain (fHbp ID 14) and from an endemic United Kingdom strain (ID 15) showed 10-fold lower fH binding than a reference fHbp from an epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 29 publications
5
25
0
Order By: Relevance
“…3A), as we had observed previously (31). Based on the FH concentrations needed to obtain an optical density of 1.0 (Fig.…”
Section: Resultssupporting
confidence: 50%
“…3A), as we had observed previously (31). Based on the FH concentrations needed to obtain an optical density of 1.0 (Fig.…”
Section: Resultssupporting
confidence: 50%
“…Given this significant overlap, it is not surprising that the binding of fHbp to fH was inhibited by addition of mAb 12C1, although structural data show that Fab 12C1 is not a structural mimic of fH. Moreover, the affinity of fHbp to mAb 12C1 (K D < 0.05 nM) is remarkably higher than the affinity reported for fHbp to hfH (5-45 nM) (22,27,32,33), thus explaining the observed capacity of mAb 12C1 to displace fH from the fHbp:hfH complex. The crystal structure, together with multiple sequence alignments, also indicated a subset of fHbp residues potentially responsible for the var1 binding specificity of mAb 12C1.…”
Section: Discussionmentioning
confidence: 78%
“…4B and C), suggested that fH interactions were fundamentally different between the different fHbp variant groups. In previous studies, binding affinities of fH to fHbp also were reported to be higher for sequence variants in variant groups 2 and 3 than in variant group 1 (17,50), which also suggested that the fH-binding modes may be different between fHbp variants. Using a structural homology modeling approach, we identified 63 residues that potentially played a role in the interaction of fHbp with human fH.…”
Section: Discussionmentioning
confidence: 99%